Fetal Heart Rate Patterns in Monochorionic Twins Following Acute Twin-Twin Transfusion - Shunji Suzuki; Nao Iwasaki; Shuichi Ono; Miwa Igarashi; Tomoaki Murata (Obstetrics and Gynecology International)
Background. We present here 2 cases of acute twin-twin transfusion occurred during vaginal labor in monochorionic-diamniotic twin pregnancies. Case. Fetal heart rate tracings showed tachycardia in the donor twin in the first case, while they showed reassuring patterns in both twins in the second case. Conclusion. These differences in changes of fetal heart rate in the donor twins following acute twin-twin transfusion may be resulted from the differences in amount of transfusion and elapsed time.